MicroRNAs in Sarcopenia: A Systematic Review - Yanai, Katsunori; Kaneko, Shohei; Ishii, Hiroki; Aomatsu, Akinori; Ito, Kiyonori; Hirai, Keiji; Ookawara, Susumu; Ishibashi, Kenichi; Morishita, Yoshiyuki (Frontiers in Medicine, 2020)
Sarcopenia, which is characterized by the loss of skeletal muscle, has been reported to contribute to development of physical disabilities, various illnesses, and increasing mortality. MicroRNAs (miRNAs) are small non-coding RNAs that inhibit translation of target messenger RNAs. Previous studies have shown that miRNAs play pivotal roles in the development of sarcopenia. Therefore, this systematic review focuses on miRNAs that regulate sarcopenia.